Peran dan Kendala Orang Tua Dalam Pendampingan Pembelajaran Siswa Pendidikan Agama Kristen Dimasa Pandemi Covid-19 - Desserly Krismawaty Wesly; Edi Sujoko; R Riniwati (Sekolah Tinggi Teologi Simpson Ungaran, 2021)
The role of parents is a determining element of student success during the Covid-19 pandemic. Achieving success in children's education cannot be separated from the vital role of parents, who are the primary source in children's education. The research question is: What is parents' role in Christian Religious Learning during the Covid-19 pandemic at SDN 02 Kalirejo in the 2019/2020 academic year? The method used in this research is descriptive qualitative. The results of this study indicate that parents act as teachers, motivators, facilitators, and mentors. Then it was also found that not all parents of students have played their role in the distance learning process during the Covid-19 pandemic. This is due to several factors, including an incomplete understanding of the role of parents in the distance learning process; minimal socialization about the role of parents in distance learning either from schools or educators; distance learning is new for parents; working parents cause the time allocation to be minimal.Â